At home and at risk: The experiences of Irish adults living with obesity during the COVID-19 pandemic. (September 2022) - Farrell, Emma; Hollmann, Eva; Roux, Carel Le; Nadglowski, Joe; McGillicuddy, Deirdre
Summary: Background: People living with obesity are at elevated risk of hospitalisation, serious illness and mortality due to COVID-19. Little is known about their experience of living with obesity during the pandemic and its associated stay-at-home orders. This study sought to understand the experiences of people living with obesity during the COVID-19 pandemic. Methods: A stratified sample of Irish adults ( n  = 15) living with obesity engaged in open, phenomenological, interviews and a participatory photovoice methodology to capture both verbal and visual accounts of their experiences during the COVID-19 pandemic. Interviews, conducted throughout 2021, were transcribed verbatim and analysed thematically. Findings: Two overarching themes were identified. A) The pandemic and associated stay-at-home orders had a positive impact on the health and well-being of some participants; a negative impact on others; and this impact changed over time as the pandemic progressed. B) People living with obesity reported feeling stigmatised and 'othered' by their 'at risk' categorisation. Public health messaging and public discourse relating to obesity resulted in some people feeling segregated and punished by society. Interpretation: Changes in lifestyle initiated by the pandemic's stay-at-home orders had a varied impact on the health behaviours and outcomes of people with obesity. This variance offers helpful insight into the psychosocial aspects of obesity. Furthermore, the 'othering' effect of public health messaging during the pandemic warrants caution in light of the already stigmatised nature of this disease. Funding: This study is part of the SOPHIA project which received funding from the Innovative Medicines Initiative 2 Joint Undertaking under grant agreement No 875534.